Analysis of the Quality of Population Administration Services in Increasing Public Satisfaction In South Tangerang City - Dewi Wulandari; Muchlis Hamdi; Widodo Sigit (Jurnal Scientia, 2024)
The aim of this research is to find out and analyze the quality of population administration services, supporting and inhibiting factors for the quality of population administration services and to find out and analyze strategies for overcoming obstacles to the quality of population administration services provided by the Population and Civil Registration Service in increasing public satisfaction in South Tangerang City. The research method uses a qualitative approach, data collection techniques are observation, interviews and documentation. The results of this research are: 1) The quality of population administration services provided by the Department of Population and Civil Registration of South Tangerang City has not been effective. This refers to the research results, it is known that of the 5 (five) aspects of service quality, only the reliability aspect has been achieved. running effectively, while 4 (four) other indicators of service quality have not run effectively, namely direct evidence (tangibles), responsiveness, assurance and empathy. 2) There are 5 (five) supporting factors: (a ) Availability of legality, legal umbrella, SOP, technical guidelines, (b) Availability of opportunities for recruiting contract workers and honorary workers, (c) Available training institutions owned by the South Tangerang City government and privately owned, as well as opportunities for educational assistance from companies (CSR), ( d) Availability of internal government supervisory institutions and external supervisory institutions (e) Availability of sophisticated technology. There are 5 (five) inhibiting factors (a) Limited human resources, (b) Limited budget, (c) Human resource development is less than optimal (d) Limited work facilities and service facilities, (e) Weak supervision. 3) Strategies to overcome obstacles to the quality of population administration services, namely 1) Increasing the quantity and quality of human resources, 2) Fulfilling service and work facilities through increasing the budget, 3) Increasing the frequency of supervision, 4) Improving the behavior and professionalism of the apparatus.